2001
DOI: 10.1063/1.1409575
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence performance of pulsed-laser deposited Al2O3 thin films with large erbium concentrations

Abstract: Erbium doped Al 2 O 3 films with concentrations up to 6ϫ10 20 Er cm Ϫ3 have been prepared in a single step process by pulsed-laser deposition. Alternate ablation of Al 2 O 3 and Er targets has been used to control the in-depth distribution and in-plane concentration of Er 3ϩ ions independently. The characteristic Er 3ϩ photoluminescence response at 1.53 m has been studied as a function of the Er 3ϩ distribution. It is found that lifetime values can be greatly increased by increasing the Er 3ϩ-Er 3ϩ in-depth se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 25 publications
3
43
0
Order By: Relevance
“…9 In our previous works we have shown that alternate pulsed laser deposition ͑PLD͒ from the host ͑Al 2 O 3 ͒ and dopant rare earth ͑RE͒ targets can be used to obtain artificial structures in which the RE concentration and ion distribution are controlled. 10,11 An ArF excimer laser ͓ = 193 nm, = 20 ns full width at half maximum ͑FWHM͒, 2 J cm −2 ͔ was used to ablate independently the Al 2 O 3 and RE targets. The films were designed to have a 300 nm total thickness.…”
mentioning
confidence: 99%
“…9 In our previous works we have shown that alternate pulsed laser deposition ͑PLD͒ from the host ͑Al 2 O 3 ͒ and dopant rare earth ͑RE͒ targets can be used to obtain artificial structures in which the RE concentration and ion distribution are controlled. 10,11 An ArF excimer laser ͓ = 193 nm, = 20 ns full width at half maximum ͑FWHM͒, 2 J cm −2 ͔ was used to ablate independently the Al 2 O 3 and RE targets. The films were designed to have a 300 nm total thickness.…”
mentioning
confidence: 99%
“…In this way the deposition conditions for each target are controlled separately. 11,12 The schematic structure of the films is shown in the inset of Fig. 1 11,12 For the Si deposition 500 pulses on the Si target have been used in order to induce the formation of Si NPs in situ following a Wolmer-Weber growth mode, as has been reported for metal NPs such as Cu and Ag.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 The schematic structure of the films is shown in the inset of Fig. 1 11,12 For the Si deposition 500 pulses on the Si target have been used in order to induce the formation of Si NPs in situ following a Wolmer-Weber growth mode, as has been reported for metal NPs such as Cu and Ag. 13,14 Finally, in order to obtain films with the same total thickness, and thus to compensate for the different values of s in each film, two Al 2 O 3 buffer layers of thickness t have been deposited, one next to the substrate and another capping the film.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations